Key for identification of the ladybirds (Coleoptera: Coccinellidae) of European Russia and the Russian Caucasus (native and alien species) - Bieńkowski, A.o. (Zootaxa, 2018)
Although ladybirds of European Russia and the Caucasus have been the subject of numerous ecological and faunistic investigations, there is an evident lack of appropriate identification keys. New, original keys to subfamilies, tribes, genera, and species of ladybirds (Coccinellidae) of European Russia and the Russian Caucasus are presented here. The keys include all native species recorded in the region and all introduced alien species. Some species from adjacent regions are added. In total, 113 species are treated and illustrated with line drawings. Photographs of rare and endemic species are provided. Information on the distribution of species within the region under consideration is provided. Chilocorus kuwanae Silvestri, 1909 is recognized as a subjective junior synonym (syn. nov.) of Ch. renipustulatus (Scriba, 1791).